SPECTROPHOTOMETRIC ANALYSIS OF DESLORATADINE MULTICOMPONENT CRYSTAL FORMULATION: COMPARISON OF CONVENTIONAL METHODS AND CHEMOMETRIC ANALYSIS - Ainurofiq, Ahmad; Choiri, Syaiful (Molekul, 2020)
Multicomponent crystal (MCC) formulation consists of drug and co-former that spectrophotometrically has an interference each other. The aim of this research was to evaluate and develop the analytical method to obtain a fast, cheap, efficient, and adequate method to estimate desloratadine (DES) in MCC formulation using three different methods. Single wavelength calibration model was constructed at 290 nm, multiple component equations was obtained from 273 nm and 283 nm, and multivariate analysis consists of PLS and PCA, a chemo-metric based, assisted the model selection and model calibration. Single wavelength method and multivariate analysis model had been fully validated i.e. range, specificity, accuracy, precision, limit of detection, and limit of quantification. A multivariate analysis had more adequate ability to estimate the DES and co-former in the MCC formulation.Keywords: Desloratadine, multicomponent crystal, multivariate, PLS